Pengaruh Kompetensi dan Motivasi Kerja terhadap Kinerja Karyawan: The Influence of Work Competency and Motivation on Employee Performance - Benedictus Kristo Wijayanto; Asri Laksmi Riani (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
Employee performance has a contribution to the development of a company. The personal performance of an employee can influence by competency and work motivation factors. This research was arranged based on theoretical analysis as well as empirical studies. The research aims to define a structured thinking concept about the relationship between competency variables, work motivation, and employee performance. Worker performance is the result of efforts achieved by a person or group who work in a company. Then competence leads to the employee’s deep and inherent personality. Work motivation is the driving force that makes an employee use his/her abilities to complete the works. Further research can examine conceptual frameworks in business, manufacturing, and service organizations.